A CMOS mixed signal simultaneous bidirectional signaling I/O - Jackson, S.A.; Blalock, B.J. (Circuits and Systems; Proceedings: Midwest Symposium on Circuits and Systems, 1998)
Limited pin counts and achievable bandwidth have become a major limitation to achievable I/O speed of integrated circuits. Previously published current-mode techniques enable I/O circuits to achieve simultaneous bidirectional signaling. This maximizes data rate with minimal I/O power dissipation and minimal I/O pin count. A new I/O circuit fabricated in 2 /spl mu/m CMOS is described in this work which is capable of handling both analog and digital data signals in a simultaneous bidirectional manner. Mixed-signal operation is achieved by using an analog transmitter to steer current in and out of a transmission line with a receiver amplifier recovering the receive signal.